Utopie, pragmatopie et hétérotopie. À propos de quelques limites politiques des expérimentations de transition écologique - Bruno Villalba (Développement Durable et Territoires)
Concrete utopias are embedded in a pre-existing theoretical and political framework that helps shape their perspectives of action. The use of the notions of pragmatopia and heterotopia allows us to take a reflexive look at the relationship that ecological transition experiments maintain, internally and externally, with political power. We can thus question the limits of the insularity of utopias, their relationality and the complex relationship between individual and community.